Identification microbial glycans substructure associate with disease and species. (1st December 2021) - Li, Kun; Liu, Xiaoyu; Zhang, Xunlian; Liu, Zhaoxi; Yu, Yue; Zhao, Jiayu; Wang, Lushan; Kong, Yun; Chen, Min
Abstract: The microbial glycans mediate many significant biological acts, such as pathogen survival, host-microbe interactions, and immune evasion. The systematic study of microbial glycans structure remains challenging because of its high complexity and variability. In this study, we screened all the microbial glycans structures in the CSDB (Carbohydrate Structure Database), disassembled them into substructures, and calculated all the substructures' numbers. The results showed that a large number of glycan substructures are shared among different microorganisms. Further analysis showed that the glycan substructures appeared in specific bacterial groups may be related to the species and pathogenicity of microorganisms. Broadly, these findings provided an alternative approach or clue to discover the hidden information and the biological functions of glycans. The results can be used to detect broad-scope pathogen or prepare broad-spectrum vaccines. Highlights: Use substructure statistics to reveal the hidden information of glycans Glycan substructure of bacteria associated with disease Glycan substructures related to microbial classification